Levantamento da vegetação da Caatinga utilizada na alimentação animal no oeste potiguar - Ferreira, Francisca Wegna da Silva (Universidade Federal Rural do Semi-Árido, 2014)
The objective of this study was identify within the adopted managements systems, information about forage species used in animal feed in the regions of Chapada do Apodi and Seridó, according to information from the farmers through questionnaires analyzed using the multivariate technique. 100 properties were visited in each region, from May to June 2013.The questionnaire containing 19 questions, six objective questions and thirteen discursive questions, were applied to each property in order to obtain information about production systems and the plant species used in each region. Upon completion of the interviews, was made the multivariate analysis using Cluster Analysis (CA) and Principal Component Analysis (PC) aimed to correlate and group the forage species according to number of citations by producers, indicating presence or absence in the systems production (intensive, semi-intensive, extensive) used in the properties. In the region of the Chapada do Apodi, jurema preta(Mimosa tenuiflora,(Willd.), jucá (Libidibia ferrea (Mart. exTul.) L.P. Queiroz), juazeiro (Ziziphus joazeiro, Mart),mororó (Bauhinia cheilantha, (Bong) Stend) and catingueira (Caesalpinapyramidalis) were the most cited species for use in animal feed, and these same species were more represented in extensive and semi-intensive system, in that order. In this region were mentioned the carnauba (Copernica cerifera Mart),macambira (Bromeliala ciniosa) and the Xiquexique (Pilosocereus glaucescens) as options for replacement feeding during the dry season. In Seridó the jucá (Libidibia ferrea (Mart. exTul.) L.P. Queiroz), the joazeiro (Ziziphus joazeiro, Mart), the catingueira (Caesalpina pyramidalis), sucupira (Pterodonpoly galaeflorus (Benth.) and the Calumbi (Senegalia tenuifolia) were the most common species for use in animal feed, and the same were more represented in the semi-intensive system. For this area were mentioned the palma (Opuntia ssp.) and the xiquexique (Pilosocereus glaucescens) as options for alternative food during the dry season. The salsa (Petroselinum crispum (Mill.) and the pereiro (Aspidosperma pyrifolium, Mart.) were cited as toxic plants to animals in the two regions. Thus, it was observed that the studied regions have species with potential for animal feed, encouraging the search for more studies and therefore the sustainable use and exploitation of these species. Keywords: Family agriculture, forage species, rural properties, Semiarid
Research of caatinga vegetation used in animal feeding in the western region of the RN
Keywords: Family agriculture; forage species; Caatinga; semiarid; Agricultura familiar; Espécies forrageiras; Caatinga; Semiárido; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL